Laser Improves Biogas Production by Anaerobic Digestion of Cow Dung - Baghdad Science Journal (مجلة بغداد للعلوم)
This study investigates the digestion of cow dung (CD) for biogas production at laboratory scales. The study was carried out through anaerobic fermentation using cow dung as substrate. The digester was operated at ambient temperatures of 39.5 °C for a period of 10 days. The effect of iron powder in controlling the production of hydrogen sulfide (H2S) has been tested. The optimum concentration of iron powder was 4g/L with the highest biogas production. A Q – swatch Nd:YAG laser has been used to mix and homogenize the components of one of the six digesters and accelerate digestion. At the end of digestion, all digestions effluent was subjected to 5 laser pulses with 250mJ/pules to dispose waste biomass.